Optical radiation special features from plasma of low pressure discharge initiated by microwave radiation with stochastic jumping phase - Karas, V.I.; Alisov, А.F.; Bolotov, О.V.; Golota, V.I.; Karas, I.V.; Yegorov, А.М.; Zagorodny, A.G.; Zagrebelny, I.А.; Potapenko, I.F. (Вопросы атомной науки и техники, 2013)
We study the plasma discharge, initiated by microwave radiation with stochastically jumping phase (MWRSJP) in a coaxial waveguide at the optimal mode of the beam-plasma generator. Present results continue the line of the previous research. In this paper we experimentally examine the optical characteristics of the discharge plasma in a wide range of both an air pressure and microwave radiation power. In general the research aims to develop a new type of sources of optical radiation.